2007
DOI: 10.3892/ijo.30.6.1485
|View full text |Cite
|
Sign up to set email alerts
|

LH-RH receptors in human colorectal cancers: Unexpected molecular targets for experimental therapy

Abstract: Abstract. Since the efficacy of chemotherapy can be enhanced by targeting to specific receptors on tumors, we investigated the expression of LH-RH receptors in 5 human colon cancer lines and the effects of cytotoxic LH-RH analogs on these tumors. Nude mice bearing HT-29, HCT-116, HCT-15, LoVo and Colo-320DM cancers were treated with cytotoxic LH-RH analogs AN-152 and AN-207 or their respective cytotoxic radicals doxorubicin (DOX) and 2-pyrrolino-DOX (AN-201). The reduction in tumor growth was evaluated, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 40 publications
(101 reference statements)
2
39
0
Order By: Relevance
“…These include liver (63), larynx (64), pancreas (65), colon (66), lymphoma (67), kidney (68,69), skin (70,71), leukemia (49) and brain (72). The function of GnRH and GnRHR in these tumors has been associated with inhibition of proliferation in a time-and dose-related manner in respond to various molecular form of GnRH (63)(64)(65)(66)(67)(68)(69)(70)(71)(72). The response to GnRH in pancreatic tumors has been shown to be specific, it was demonstrated by the absences of binding sites for GnRH in membranes from nontumoral human pancreas tissues (65,73).…”
Section: Function Of Gnrhr In Tumors From Non-reproductive Tissuesmentioning
confidence: 99%
“…These include liver (63), larynx (64), pancreas (65), colon (66), lymphoma (67), kidney (68,69), skin (70,71), leukemia (49) and brain (72). The function of GnRH and GnRHR in these tumors has been associated with inhibition of proliferation in a time-and dose-related manner in respond to various molecular form of GnRH (63)(64)(65)(66)(67)(68)(69)(70)(71)(72). The response to GnRH in pancreatic tumors has been shown to be specific, it was demonstrated by the absences of binding sites for GnRH in membranes from nontumoral human pancreas tissues (65,73).…”
Section: Function Of Gnrhr In Tumors From Non-reproductive Tissuesmentioning
confidence: 99%
“…Specific receptors for LHRH were detected on human breast, prostatic, ovarian, endometrial and pancreatic cancers (8)(9)(10)(11)(12)(13)(14)(15)(16). In an unselected series of human breast cancer samples (containing steroid receptor positive and negative as well as HER2-positive and -negative samples) our group detected high-affinity binding sites for LHRH in >50% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Specific receptors for luteinizing hormone-releasing hormone (LHRH) have been so far detected on a variety of human cancer cells, such as breast, prostatic, ovarian, endometrial, colorectal and pancreatic cancers as well as melanomas and non-Hodgkin's lymphoma (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The production of an LHRH-like peptide and/or the expression of mRNA for LHRH was also demonstrated in various human cancer cell lines (8,14,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, their expression on sarcomas, with the exception of endometrial sarcomas, has not been studied. It has been demonstrated that both LHRH agonists and antagonists can inhibit the growth of these tumor cells [17][18][19]. A further major therapeutic implication is that the cells expressing these receptors can be targeted even more effectively by conjugating cytotoxic moieties to the LHRH agonists, a 3rd type of analog.…”
Section: Introductionmentioning
confidence: 99%